Strengthening Internal Audit Functions in Local Government: An IACM-Based Assessment of the Pinrang Regency Inspectorate - Yasri Tarawiru; Jumriani; Nur Fatwa Basar; Andi Sri Kumala Putri; Rika Rahma (IECON: International Economics and Business Conference, 2025)
This study analyzes the APIP capability in the Pinrang Regency Inspectorate using the IACM standard. The purpose of this study is to analyze the level of competence of the Government Internal Supervisory Apparatus (APIP) in the Pinrang Regency Inspectorate using the Internal Audit Capability Model (IA-CM), identify factors that influence APIP performance, and develop strategies to improve APIP competence. The method used is descriptive research with data collection techniques through observation, documentation, and interviews, followed by descriptive analysis. The results of the study indicate that the APIP capability of the Pinrang Regency Inspectorate is at level 3 based on IA-CM. Of the six elements of internal audit, five elements: APIP Role and Services, Organizational Culture and Relationships, and Governance Structure have reached level 3, while the Human Resource Management element has reached level 4. The main limitation lies in the elements that are still at level 3, so improving APIP competence is a priority. The Inspectorate has developed a strategy to strengthen Key Process Areas (KPA) to encourage increased capabilities to a higher level.